Profitability of forage production in smallholder peri-urban dairy production systems - Agyemang, K.; Dogoo, D.L.; Makun, H.J. (Cambridge University Press, 1998)
Peri-urban dairy producers in West Africa face major production constraints including inadequate and poor quality feeds. In view of the high cost of traditional supplementary feeds such as oilseed cakes, the production of forage, especially legumes, is increasingly being advocated. However, it has not been established whether returns in terms of increased livestock productivity from sown forages will be adequate to encourage smallholder livestock owners to undertake forage production for indigenous livestock. In three trials involving indigenous Bunaji cows biological and economic responses in terms of milk yields to farmer-planted forage legumes and tree legumes from home gardens were evaluated. Synthesis of the resulting data on labour inputs, forage yields, feed intakes, milk yields, value of outputs and cost of inputs such as seeds and fertilizers showed that for the semi-intensive smallholder and zero-grazed models considered in this study, the margin or profit from using home-grown fodder was 5-8 times the cost of acquiring the feed. The opportunity cost of using the land for forage production rather than for cultivating sorghum, a highly favoured cereal crop, was only 67 percent of the accrued benefits from milk yields produced by cows supplemented with the forage hays. Thus, there is a real potential for profitable dairy production in peri-urban areas using home-grown fodder.